Iodine-Catalyzed C–N Cleavage of Tertiary Amines: Synthesis of Methylene-Bridged Bis-1,3-dicarbonyl Compounds - Lu, Lin; Guo, Shengmei; Xiong, Qiheng; Liu, Shengyi; Li, Xiang; Cai, Hu (Synthesis, 2014)
A novel and efficient iodine-catalyzed C–N cleavage of tertiary amines via an sp3 C–H bond oxidative coupling reaction is described. A wide range of methylene-bridged bis-1,3-dicarbonyl compounds were synthesized in up to 92% yield by using an environmentally benign catalytic system in combination with 1,3-dicarbonyl compounds.
Keywords: iodine; oxidative coupling; C–N cleavage; tertiary amines; methylene-bridged bis-1,3-dicarbonyl compounds